The impacts of new neighborhoods on poor families: evaluating the policy implications of the moving to opportunity demonstration - John Goering
This paper was presented at the conference "Policies to Promote Affordable Housing," cosponsored by the Federal Reserve Bank of New York and New York University's Furman Center for Real Estate and Urban Policy, February 7, 2002. It was part of Session 3: The Impact of Housing on People and Places.Housing ; Housing policy ; Poverty ; Demography